(untitled) (Medico Legal Update, 2021)
Objective: To evaluated outcome transcatether PDA closure and differentiated LVEDD, EF pre and post transcatether PDA closure. Methods: Hospital registry was reviewed and data about patients characteristics, PDA size, device occluder and outcomes were retrieved. An descriptive analytic study with a retrospective design was conducted on all medical records of PDA pediatric patients who received definitive transcatheter PDA closure at IDIK and were treated at the Department of Child Health, Dr. Soetomo Hosptal from January 2017 until December 2019. The variables studied are: outcome transcatether PDA closure (complete closure, residual shunt, emboli device, obstruction pulmonaly artery, obstruction Aorta descendent, hemolysis, LVEDD and EF). Post catheterization included a follow up of immediately, 1 day, 1 month, 3 months, 6 months, and 12 months after catheterization. The data were processed and statistical comparative tests were carried out. Results: There were 101 subjects, of whom were 33 males, who underwent transcatether closure of PDA during study periode. The diameter PDA ranged from 1-7.5 mm, with median 3.4 mm. Median age 4.3 years (4 months-18 years), median body weight was 15.4 (5 – 45) kg. Device could be deployed in all patients, in which ADO I 65%, ADO II 15%, Nit Occlude 2% and MFO 19%. Immediately Complete closure was achieved in most patiens (92,1%) and small residual shunt (7,9%), no major complication during or after procedure. Most patient were discharged from hospital at 3 day after procedure. LVEDD and EF was decreased after intervention transcatether closure (P <0.05). There were no significant differences in LVEDD and EF transcatether based on closured method and sex. Conclusion: All patients showed complete closure during followed up. Transcatheter closure of PDA is safe and effective with shorter hospitalization and minimally complications.